The Exploratory Study on Antecedents of Online Medical Consultation Continuous Usage Intention - Larasati, Andini; Antonio, Ferdi; Wuisan, Dewi (Jurnal Kesehatan Masyarakat, 2024)
The purpose of this study is to find and analyze factors that can affect Intention to Recommend in online medical consultation field. The research model is adapted from a previous study and then modified. Data were collected from women that are 17 years old and who have ever used the online medical consultation application, Halodoc. The research’s method is a quantitative survey, with cross-sectional data. Respondents’ data were taken by purposive sampling and questionnaires were distributed online. As many as 202 participants have fulfilled the requirements to be analyzed with PLS-SEM. The results showed that five antecedents had a significant influence on Intention to Recommend. Antecedents that were worth noting were Helpfulness Trust, Perceived Benefit, and Reliability Trust, where these factors show a positive impact on Intention to Recommend. Factors that could potentially influence users not using online medical consultation applications were also found, such as Performance Risk and Privacy Risk. From the findings of this study, it can be concluded that there are factors that may need to be considered by online medical consultation service providers to maintain or even to better their quality of care.